Comparative study and simulation of advanced MPPT control algorithms for a photovoltaic system - Ismail Isknan; Abdellah Asbayou; Abdel Hamid Adaliou; Ahmed Ihlal; Lahoussine Bouhouch (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
A photovoltaic (PV) system uses solar radiation and converts it into electrical energy. An energy management system consisting of a maximum power point tracking (MPPT) charge controller is then necessary. In the present work, for the optimization of the electrical energy delivered by the solar PV panel we will compare four types of controls explained below, namely "MPPT-P&OM", "MPPT-IncM", "MPPT-PI-P&OC" and "MPPT-FOPI-P&OC". Based on these comparisons, for different values of solar irradiance, the four methods seem to perform quite similarly; all four are fast and show small oscillations around the optimal value; nevertheless, the MPPT-IncM method performs slightly better than the others. This is due to the fact that it is slightly faster and has fewer oscillations. The simulation is implemented numerically using the MATLAB/Simulink development tool.